Trends in obesity and adiposity measures by race or ethnicity among adults in the United States 2011-18: population based study - Liu, Buyun; Du, Yang; Wu, Yuxiao; Snetselaar, Linda G; Wallace, Robert B; Bao, Wei (BMJ (Online), 2021)
AbstractObjectiveTo examine the trends in obesity and adiposity measures, including body mass index, waist circumference, body fat percentage, and lean mass, by race or ethnicity among adults in the United States from 2011 to 2018.DesignPopulation based study.SettingNational Health and Nutrition Examination Survey (NHANES), 2011-18.ParticipantsA nationally representative sample of US adults aged 20 years or older.Main outcome measuresWeight, height, and waist circumference among adults aged 20 years or older were measured by trained technicians using standardized protocols. Obesity was defined as body mass index of 30 or higher for non-Asians and 27.5 or higher for Asians. Abdominal obesity was defined as a waist circumference of 102 cm or larger for men and 88 cm or larger for women. Body fat percentage and lean mass were measured among adults aged 20-59 years by using dual energy x ray absorptiometry.ResultsThis study included 21 399 adults from NHANES 2011-18. Body mass index was measured for 21 093 adults, waist circumference for 20 080 adults, and body fat percentage for 10 864 adults. For the overall population, age adjusted prevalence of general obesity increased from 35.4% (95% confidence interval 32.5% to 38.3%) in 2011-12 to 43.4% (39.8% to 47.0%) in 2017-18 (P for trend<0.001), and age adjusted prevalence of abdominal obesity increased from 54.5% (51.2% to 57.8%) in 2011-12 to 59.1% (55.6% to 62.7%) in 2017-18 (P for trend=0.02). Age adjusted mean body mass index increased from 28.7 (28.2 to 29.1) in 2011-12 to 29.8 (29.2 to 30.4) in 2017-18 (P for trend=0.001), and age adjusted mean waist circumference increased from 98.4 cm (97.4 to 99.5 cm) in 2011-12 to 100.5 cm (98.9 to 102.1 cm) in 2017-18 (P for trend=0.01). Significant increases were observed in body mass index and waist circumference among the Hispanic, non-Hispanic white, and non-Hispanic Asian groups (all P for trend<0.05), but not for the non-Hispanic black group. For body fat percentage, a significant increase was observed among non-Hispanic Asians (30.6%, 29.8% to 31.4% in 2011-12; 32.7%, 32.0% to 33.4% in 2017-18; P for trend=0.001), but not among other racial or ethnic groups. The age adjusted mean lean mass decreased in the non-Hispanic black group and increased in the non-Hispanic Asian group, but no statistically significant changes were found in other racial or ethnic groups.ConclusionsAmong US adults, an increasing trend was found in obesity and adiposity measures from 2011 to 2018, although disparities exist among racial or ethnic groups.